Random Phase Approximation Applied to Many-Body Noncovalent Systems - Modrzejewski, Marcin; Yourdkhani, Sirous; Klimeš, Jiří (Journal of chemical theory and computation, 2020)
The random phase approximation (RPA) has received considerable interest in the field of modeling systems where noncovalent interactions are important. Its advantages over widely used density functional theory (DFT) approximations are the exact treatment of exchange and the description of long-range correlation. In this work, we address two open questions related to RPA. First, we demonstrate how accurately RPA describes nonadditive interactions encountered in many-body expansion of a binding energy. We consider three-body nonadditive energies in molecular and atomic clusters. Second, we address how the accuracy of RPA depends on input provided by different DFT models, without resorting to self-consistent RPA procedure, which is currently impractical for calculations employing periodic boundary conditions. We find that RPA based on the SCAN0 and PBE0 models, that is, hybrid DFT, achieves an overall accuracy between CCSD and MP3 on a data set of molecular trimers from Řezáč et al. ( J. Chem. Theory. Comput. 2015 , 11 , 3065 ). Finally, many-body expansion for molecular clusters and solids often leads to a large number of small contributions that need to be calculated with high precision. We therefore present a cubic-scaling (or self-consistent field (SCF)-like) implementation of RPA in atomic basis set, which is designed for calculations with high numerical precision.